2023
DOI: 10.1007/s13593-023-00912-w
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon stock change following perennialization: a meta-analysis

Imran Ahammad Siddique,
Diego Grados,
Ji Chen
et al.

Abstract: Perennial crops replacing annual crops are drawing global attention because they harbor potential for sustainable biomass production and climate change mitigation through soil carbon sequestration. At present, it remains unclear how long perennial crops can sequester carbon in the soil and how soil carbon stock dynamics are influenced by climate, soil, and plant properties across the globe. This study presents a meta-analysis synthesizing 51 publications (351 observations at 77 sites) distributed over differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…A recent meta‐analysis by Siddique et al. (2023) further underscored that short‐term changes following such conversions are often a decline rather than an increment, suggesting it could take up to 5 years with the perennials to see the benefits over the previous annual crops in terms of the soil carbon storage. However, such impacts may be limited to only the surface layer (0–5 cm depth).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta‐analysis by Siddique et al. (2023) further underscored that short‐term changes following such conversions are often a decline rather than an increment, suggesting it could take up to 5 years with the perennials to see the benefits over the previous annual crops in terms of the soil carbon storage. However, such impacts may be limited to only the surface layer (0–5 cm depth).…”
Section: Resultsmentioning
confidence: 99%
“…A previous global assessment of SOC changes after the conversion of annual crops to perennial crops by Ledo et al (2020) also revealed the possibility of a temporary decline in SOC content. A recent meta-analysis by Siddique et al (2023) further underscored that short-term changes following such conversions are often a decline rather than an increment, suggesting it could take up to 5 years with the perennials to see the benefits over the previous annual crops in terms of the soil carbon storage. However, such impacts may be limited to only the surface layer (0-5 cm depth).…”
Section: Kernza and Alfalfa Effects On Socmentioning
confidence: 99%
“…However, in sites previously managed as grassland, this mechanism of C compensation requires more time to occur. According to the meta-analysis of Siddique et al (2023), the change of SOC stock under perennial crops follows a sigmoidal curve over time. The increase in SOC with perennial crops like Miscanthus started after approximately 5 years, compensating for losses of original SOC caused by soil disturbance, soil priming and lower productivity of newly established crops.…”
Section: Soc Sequestration and Its Driversmentioning
confidence: 99%
“…The results derived from the study indicated that heavy logging led to increased soil N 2 O emissions [30]. And in 2023, Siddique et al [31] employed meta-analysis methods to examine the effect of perennialization on organic carbon accumulation in soil. Their research findings indicate that the duration since conversion from an annual to a perennial system significantly increased soil organic carbon stock by 16.6% and 23.1% at depths of 0-30 cm compared with monoculture and crop rotation, respectively.…”
Section: Introductionmentioning
confidence: 99%